Replication, falsification, and the crisis of confidence in social psychology - Earp, Brian D.; Trafimow, David (Frontiers in Psychology, 2015)
The (latest) crisis in confidence in social psychology has generated much heated discussion about the importance of replication, including how it should be carried out as well as interpreted by scholars in the field. For example, what does it mean if a replication attempt “fails”—does it mean that the original results, or the theory that predicted them, have been falsified? And how should “failed” replications affect our belief in the validity of the original research? In this paper, we consider the replication debate from a historical and philosophical perspective, and provide a conceptual analysis of both replication and falsification as they pertain to this important discussion. Along the way, we highlight the importance of auxiliary assumptions (for both testing theories and attempting replications), and introduce a Bayesian framework for assessing “failed” replications in terms of how they should affect our confidence in original findings.